Pengaruh Profitabilitas, Capital Intensity, Likuiditas Dan Biaya Operasional Terhadap Pajak Penghasilan Badan Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bei Periode 2015-2020 - cici wulandari; farida khairani; zufrizal zufrizal; masut masut (Universitas Islam Islam Sumatera Utara, 2022)
The purpose of this study is to test and analyze the effect of profitability on corporate income tax, to test and analyze the effect of capital intensity on corporate income tax, to test and analyze the effect of liquidity on corporate income tax, to test and analyze the effect of operating costs on corporate income tax. , to test and analyze the effect of profitability, capital intensity, liquidity and operating costs on corporate income tax in Food and Beverage Companies Listed on the IDX. The population in this study were all Food and Beverage Companies listed on the BEI as many as 24 companies and samples from research on Food and Beverage Companies were 8 companies with 6 years of observation. The data collection technique used in this research is documentation. The analysis technique used in this research is descriptive statistics, multiple linear regression analysis, partial test, and determinant test. The results showed that profitability positive and significant effect on Corporate Income Tax, Capital Intensity negative and significant effect on Corporate Income Tax, Liquidity negative and significant effect on Corporate Income Tax, Operational Costs partially had a positive and significant effect on Corporate Income Tax. Corporate Income Tax, and that profitability, capital intensity, liquidity and operating costs have a significant effect on Corporate Income Tax in Food and Beverage Companies Listed on the Indonesia Stock Exchange for the 2015-2020 Period.